2001
DOI: 10.4049/jimmunol.167.2.855
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Characteristics of the IFN-γ Reporters in Nontransformed T Cells

Abstract: Analysis of the IFN-γ promoter has primarily been conducted by transient expression of reporter constructs in transformed cells. However, the activity of cis elements may differ when expressed transiently compared with their activity within native chromatin. Furthermore, the transcription factors and signaling mechanisms in transformed cells may differ from those in normal T cells. To analyze IFN-γ promoter regulation in normal T cells, we developed a novel retroviral bottom-strand reporter system to allow the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 47 publications
(52 reference statements)
0
28
0
Order By: Relevance
“…Our reporter analyses indicated that GATA-3 transactivates all of the IL-5, IL-4, and IFN-␥ promoters in Jurkat cells (15,51), differently from EL-4 cells or Th2 cells (11,13). The short fragment of the IFN-␥ promoter does not behave in parallel with the endogenous IFN-␥ gene (52), and there is also evidence that the expression of IFN-␥ gene is regulated at the chromatin accessibility (21), which cannot be reflected by reporter assays. Our reporter assays revealed that FOG represses the GATA-3-mediated transactivation of all the cytokine promoters, including IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Our reporter analyses indicated that GATA-3 transactivates all of the IL-5, IL-4, and IFN-␥ promoters in Jurkat cells (15,51), differently from EL-4 cells or Th2 cells (11,13). The short fragment of the IFN-␥ promoter does not behave in parallel with the endogenous IFN-␥ gene (52), and there is also evidence that the expression of IFN-␥ gene is regulated at the chromatin accessibility (21), which cannot be reflected by reporter assays. Our reporter assays revealed that FOG represses the GATA-3-mediated transactivation of all the cytokine promoters, including IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this methylation site is evolutionarily conserved, because it is present in other vertebrates with the exception of avians (47). Regardless, the proximal promoter regions important for TCRinduced activation are not sufficient for normal tissue-specific expression or cytokine-induced IFNG gene induction (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vivo control of IFN-␥ transcription is likely to involve the cooperative effects of regions both proximal and distal to the IFNG gene (8). Accordingly, the 5Ј-flanking region of the IFNG gene has been suspected of harboring crucial regulatory elements (9), and a PHA/PMA-inducible HS site estimated to be ϳ3 kb upstream was found in Jurkat T cells in 1987 (28). A recent paper by Lee and colleagues (60) describes a distal Th1-specific HS site that was estimated to be ϳ5 kb upstream of the murine IFNG gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DO11.10 ␣␤ TCR-transgenic mice (9,20), murine rIL-4, and rIL-12 (21) have been described. Anti-CD28 (37.51) and CD3 (500A2) were gifts from Dr. J. P. Allison (Berkeley, CA) and were purified by affinity chromatography from culture supernatant or used as ascites.…”
Section: Reagentsmentioning
confidence: 99%